Система підготовки вчителів іноземних мов у США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Видавництво СумДПУ імені А. С. Макаренка, 2020)
Резюме. Метоя статті є висвітлення структури, властивостей, елементів, компонентів, ознак і принципів системи підготовки вчителів іноземних мов у США. У дослідженні застосовано метод системного аналізу. Структуру системи підготовки вчителів-філологів складаю мережа закладів освіти. Система функціонує на різних рівнях вищої освіти. Властивостями системи філологічної освіти є відкритість, динамічність, цілеспрямованість, адаптивність і децентралізованість; її елементами є цілі й завдання системи педагогічної освіти, зміст і мета навчання в університетах, форми організації освітнього процесу, дидактичні підходи, принципи навчання, засоби і способи здобування освіти, результати тощо. Компонентами системи є цільовий, ціннісний, нормативно-правовий, організаційно-процесуальний, змістовий, оцінювально-результативний і концептуальний.

Abstract. The paper is devoted to the study of the structure, characteristics, elements, components, features and principles of the system of foreign language teacher education in the USA. To this end, the method of systematic analysis was employed. The development of the American system of language teacher preparation has been impacted by the societal needs for foreign language specialists, the educational and language policy, scientific advancements, and general globalizing trends. The structure of the teacher education system is formed by a network of education institutions (universities, colleges, scientific centers, centers of professional development, etc.), professional organizations, advisory bodies, governing bodies, accreditation bodies. The system of teacher preparation includes the educational levels of a bachelor, master, doctor of philosophy, certification programs undergirded by the idea of lifelong learning. It has a multicomponent structure, covering legal, target, regulatory, organizational-procedural, curricular, evaluative, and conceptual components. Features of the US system of language teacher preparation that promote its coherence and dialectical interconnectivity are openness, dynamism, purposefulness, adaptability and decentralization. The system’s integrative elements are the goals and objectives of teacher preparation, the content and purpose of the university course of study, forms of organization of the processes of education and professional development, approaches to the professional competence development, didactic principles, means and ways of obtaining higher education, the educational process and its results. The underlying principles of foreign language teacher preparation are diversity and inclusion, lifelong learning, personalization together with related to it individualization and differentiation, standardization, fundamentalization, the spread of information technologies in education, collaboration, autonomy, academic integrity, academic mobility, competition and others.

Резюме. Целью статьи является изучение структуры, свойств, элементов, компонентов, признаков и принципов системы подготовки учителей иностранных языков в США. В исследовании применен метод системного анализа. Свойствами системы филологического образования является открытость, динамичность, целеустремлённость, адаптивность и децентрализованность; ее элементами являятся цели и задачи системы педагогического образования, содержание и цель обучения в университетах, формы организации образовательного процесса, дидактические подходы, принципы обучения, средства и способы получения образования, результаты и т.д. Компонентами системы являются целевой, ценностный, нормативно-правовой, организационно-процессуальный, содержательный, оценочно-результативный и концептуальный.
The system of foreign language teacher education in the USА
Система подготовки учителей иностранных языков в США
http://repository.sspu.sumy.ua/handle/123456789/9017
Keywords: система підготовки вчителів іноземних мов; університет; здобувач вищої освіти; освітня програма; іншомовна освіта; США